Computational Fluid Dynamics Analysis of a Vehicle Radiator Using Porous Media Approach. Issue 11 (17th June 2021) - Aydın, Ahmet; Engin, Tahsin; Yasar, Halit; Yeter, Alper; Perut, Ahmet Hulusi
Abstract: In this study, a cooling radiator developed specifically for unmanned aerial vehicles was analyzed using computational fluid dynamics (CFD). The radiator consisted of turbulator pins (core side) placed between two vertical columns (column side). While the air passes from the core side, the cooling fluid takes place between two streams on the column side. CFD modeling of the radiator, which was developed, prototyped, and tested by Kale Oto Radyatör Co. was performed. Modeling of the turbulators and the fins outside the radiator channels is almost impossible due to the tremendous number of required cells. Therefore, the porous media approach was adopted for the core side. Although there are some studies in the article that used porous medium approach in CFD analyses of vehicle radiators, they are generally restricted to CFD modeling of conceptual designs with no experimental validation, making their results questionable. Radiator tests and CFD results showed very good agreement. The maximum differences between experimental and CFD analyses results were 5.6% for pressure drop, 3.1% for radiator outlet temperature, and 2.9% for heat capacity. Therefore, it was concluded that a proper porous media model can be effectively used for both design and optimization considerations.